Svetovna književnost na Kranjskem - Juvan, Marko (Primerjalna književnost, 2011)
From 1828 to 1835, when Goethe was introducing his idea of world literature to the European public, in Slovenia Matija Čop and France Prešeren carried out the complex process of culturally transferring the Schlegel brothers' romantic cosmopolitanism. In this way they sought to substantiate the emerging and peripheral Slovenian literature, which was embedded in the national movement, with the universality of esthetic humanism and, through references to the repertoires of European literary traditions from Antiquity to Romanticism, to establish it as a modern classic at the world level. Čop and Prešeren carried out Goethe's idea of world literature without using this concept. However, it is highly likely that Čop also became acquainted with Goethe's first remarks on Weltliteratur.
Keywords: Čop, Matija, 1797-1835; Prešeren, France, 1800-1849; svetovna književnost; Slovene literature; slovenska književnost; romantika; Romanticism; romantično svetovljanstvo; narodna gibanja; kulturni transfer